U-PB DATINGS IN THE SODANKYLä SCHIST AREA, CENTRAL FINNISH LAPLAND - Räsänen J.; Huhma H. (My University, 2001)
The bedrock of the Sodankylä schist area consists mainly of Paleoproterozoic volcanic and sedimentary rocks penetrated by mafic and felsic intrusives. This paper reports c. 200 conventional U-Pb analyses mainly on zircon. A total of 34 samples were studied from 12 mafic intrusions, 3 granitoids, 5 metavolcanic rocks and 4 metasediments. Many samples yielded discordant and heterogeneous data, either due to inheritance or effects of metamorphism. The age results obtained suggest that a supracrustal belt running on the southwestern side of the Sodankylä schist area and continuing inside the Central Lapland Granite Complex is late Archean in origin. Besides amphibolites, it includes mainly different kinds of gneisses associated with 2775±25 Ma old felsic volcanic rocks. The Proterozoic volcanic succession starts with felsic extrusives, which have yielded an age of 2438±11 Ma and seem to be coeval with the emplacement of the layered mafic intrusions which indicate the break-up of the Archean continent at the beginning of the Proterozoic eon. The overlying volcano-sedimentary pile is penetrated by intrusive rocks of various ages. The most reliable results from maficintrusions include ages such as 2222±6 Ma (Harjunoja), 2148±11 Ma (Rantavaara), 2070±5 Ma (Ahvenselkä) and 2055±5 Ma (Rovasvaara). Accordingly, the age of deposition of the Sodankylä and Savukoski Group supracrustal rocks is considered older than 2.22 Ga and 2.05 Ga, respectively. A granodiorite associated with a gabbroic rock inside the schist area yields an age of 1891±5 Ma indicating that intrusions of the Haaparanta Suite are not restricted only to western Lapland. The 1.8 Ga thermal episode in the area is manifested by an age of 1808±8 Ma for a granite pegmatite dyke, as well as a few U-Pb ages on titanites. Several granites formed at this stage contain zircons inherited from older, presumably Archean sources.
Keywords: absolute age; U/Pb; zircon; metavolcanic rocks; intrusions; gabbros; metadiabase; granites; Paleoproterozoic; Archean; Lappi Province; Precambrian::Proterozoic::Paleoproterozoic; Precambrian::Archean; Докембрий::Протерозой::Палеопротерозойская; Докембрий::Архей